Dietary pattern trajectories in early childhood and their associations with patterns of maternal feeding practices in a multi-ethnic Asian cohort - Appannah, Geeta; Toh, Jia Ying; Lai, Jun Shi; Yong, Heng Yaw; Shariff, Zalilah Mohd; Tint, Mya Thway; Yuan, Wen Lun; Pang, Wei Wei; Godfrey, Keith M.; Tan, Kok Hian; Yap, Fabian; Lee, Yung Seng; et al. (BioMed Central Ltd, 2024)
Background: Maternal feeding practices play a major role in children’s dietary intakes. However, there is limited data on the associations between trajectories of dietary patterns (DPs) and patterns of maternal feeding practices during early childhood. Methods: Using data from a multi-ethnic Asian cohort study, namely the Growing Up in Singapore Towards healthy Outcomes (GUSTO), dietary intakes were measured using Food Frequency Questionnaires in children at 18 months, 5 and 7 years of age. Maternal feeding practices were assessed using validated questionnaires at 15 months, 3 and 5 years of age. Principal component analysis was used to derive 2 major DPs at all time-points as well as patterns of maternal feeding practices. Group-based trajectory modelling was used to identify trajectory groups for the derived DPs. Multivariable logistic regression examined associations between patterns of maternal feeding practices and DP trajectory groups. Results: Two DPs, namely the ‘healthy’ and ‘less healthy’ were consistently derived at 18 months, 5 and 7 years of age. From each DP, 2 stable DP trajectory groups were further identified between 18 months and 7 years of age. For the ‘healthy’ DP trajectory, majority of the children (Group 1) formed a consistent average adherence trajectory group (91.8%) while the remaining children (Group 2) showed a higher but decreasing adherence (8.2%) to this DP. For the ‘less healthy’ DP trajectory, most children (Group 1) formed a consistent average adherence trajectory (95.5%), while the remainder (Group 2) showed consistent higher adherence to this ‘less healthy’ DP (4.5%). Two patterns of maternal feeding practices were derived and labelled as ‘structured with autonomy support’ and ‘coercive control’, respectively, at ages 15 months, 3 and 5 years. Children whose mothers showed high adherence to the structured with autonomy support feeding practices at age 5 years were significantly more likely to be associated with the higher but decreasing ‘healthy’ DP trajectory group [OR = 3.62 (95% CI: 1.64, 7.99)]. Conclusions: A small number of children in this multi-ethnic study showed high adherence to the ‘healthy’ or ‘less healthy’ DP trajectory groups, respectively, while the majority showed average adherence to either of these trajectories. The positive association between structured with autonomy support maternal feeding practices and higher z-scores for the healthy DP trajectory highlights the importance of guiding parents on appropriate feeding practices.